How modern is Philippine agriculture and fisheries? - Briones, Roehlano M. (Philippine Institute for Development Studies, 2023)
The Agriculture and Fisheries Modernization Act (AFMA) envisions a sustainable and equitable development of the agriculture and fisheries sector. A quarter century since its passage, to what extent has the Philippine agriculture and fisheries sector been modernized? This volume assessed the implementation of AFMA programs and the sector's performance in relation to the attainment of AFMA's objectives. The analyses revealed implementation gaps and provided recommendations to address them.